Karakteristik penderita glaukoma primer sudut terbuka dan sudut tertutup di divisi glaukoma di Poliklinik Mata Rumah Sakit Umum Pusat Sanglah Denpasar periode 1 januari 2014 hingga 31 desember 2014 - Bestari Putri, Putu Giani Anabella; Sutyawan, I Wayan Eka; Triningrat, AA Mas Putrawati (E-Jurnal Medika Udayana, 2018)
Glaucoma is an eye disorder characterized by increased eye pressure, optic nerve atrophy of the optic disc, and the shrinking of the field of vision with risk factors for the increase in intraocular pressure (IOP). This study was conducted to determine the characteristics of patients with primary glaucoma in Division Glaucoma, Eye Clinic in Sanglah Hospital Denpasar in 2014 by age, sex, diagnosis, intraocular pressure, and the region distribution. The study used cross sectional descriptive study, with secondary data drawn indirectly through the register book division Glaucoma Eye Clinic Hospital Sanglah Period January 1, 2014 - 31 December, 2014. In this study, a sample of 42 people, and with 64 eyes diagnosed with primary glaucoma. The results showed:(1) patients with primary glaucoma is most often found in the age group 51-80 years by 78.5%;(2) the most frequent cases of primary glaucoma angle closure glaucoma or PACG (60.93%) compared with primary open-angle glaucoma or POAG (39.06%);(3) the average intraocular pressure in the eye larger right that is 32.38 mmHg mmHg while the average pressure of the left eye 31.3 mmHg;(4) males have a greater proportion (61.90%) compared to women (38.09 %) based on the variable gender;(5) the majority of patients with primary glaucoma cases are found to originate from Denpasar (19:04%). It can be concluded among 42 cases of glaucoma is primary with 64 eyes are involved, most characteristics of patients are men, with the most age group are 51 to 80 years, the most type of glaucoma is the angle covered, and the complaints occurred in the second eye or bilateral, intraocular pressure average on oculi dextra amounted to 32.38 mmHg and IOP oculi average on the left is equal to 31.3 mmHg and most of patient are from Denpasar. Keywords: Characteristic of Primary Glaucoma, PACG, POAG